Increasing diversity to save biodiversity: Rising to the challenge and supporting Indonesian women in conservation. Issue 6 (17th March 2021) - Poor, Erin E.; Imron, Muhammad Ali; Novalina, Rafselia; Shaffer, L. Jen; Mullinax, Jennifer M.
Abstract: Indonesia is one of the most biodiverse countries in the world yet suffers from the highest global deforestation rate. Having more diverse voices in conservation science contributing innovative ideas and solutions could benefit the country's biodiversity. However, some aspects of conservation work in Indonesia remain male‐dominated, particularly fieldwork. Understanding motivations and challenges for women pursuing a conservation career is critical to diversifying the workforce. We present some of the motivations and challenges of women conservation scientists attending a field skills and networking workshop in Sumatra, Indonesia, in September 2019. We conducted semistructured surveys in a preliminary study with female conservation scientists at the beginning of their careers and those with established careers of at least 3 years. Early‐career women predominantly cited a love of nature as their main motivator and cultural‐based gender norms as their primary challenge. Established career women discussed slowly improving gender norms and the importance of mentors throughout their careers. Without active engagement in career training and support over the long‐term for underrepresented groups in conservation, we could lose out on novel perspectives that could help solve the world's most daunting ecological problems. Abstract : As a globally important biodiversity hotspot, Indonesia may benefit from a wider diversity of voices and ideas in its male‐dominated conservation field. In this study, we held a weekend conservation skills workshop for early and established career women to network and learn, and conducted a preliminary survey identifying motivations and challenges of women working in Indonesian conservation. Participants expressed interest in future workshops, and we recommend such workshops as a way to increase participation of underrepresented groups in the conservation field.